Globalisation and managing organisational culture change: The case of Turkey - (:unkn) unknown (My University, 2004)
Globalisation has led to acceleration and vast change not only in technology and work processes, but alro in organisational culture. Organisational culture is one of the few concepts that have been variously defined in social science literature. Schein (1997) focuses on the various subsystcms in organisations whose function is to deliver the products or services stemming from the organisations basic mission. He argues that each subsystem develops its own culture, and it is those cultures that often become the primary target of organisational transformation efforts. Organisational cultures seem to have a high impact on orgnisational development. Within such a basic framework, the objective of this study is to observe and manifest the dynamics of organisational culture and change in a midsize (n = 2056), family owned industrial organisation. Both quantitative and qualitative measurement approaches are used. The results reveal that the organisational culture changed during the organisation's 40-year lifespan.